On the compactification and reformation of string theory with three large atomic gravitational constants - V.S. Seshavatharam, U.; Lakshminarayana, S. (International Journal of Physical Research, 2021)
Scientists strongly believe that, String theory is empowered with good mathematics and smartly fits gravity in unification program. Point to be noted is that, by considering the Planck length as characteristic amplitude associated with strings, String theory advances its ideological representation. Very unfortunate thing is that, even though, originally, String theory was proposed for understanding â€˜strong interactionâ€™, as Planck length is 20 orders of magnitude less than the nuclear size, it is badly failing in explaining and predicting nuclear scale physical phenomena. Here, we would like to stress the point that, within the scope of observed materialistic physical systems, without addressing the roots of H-Bar and big G, it is impossible to construct a workable model of final unification. In this context, in our earlier publications, we proposed the existence of three large gravitational constants for the three atomic interactions. Based on the three large atomic gravitational constants, it is possible to have three different workable atomic Planck amplitudes and thus there is a possibility for reforming and compactifying the 10 dimensional String theory to 3+1 dimensions. Proceeding further, H-bar can be shown to be a characteristic outcome of the electroweak interaction and big G can be shown to be a characteristic outcome of the three atomic gravitational constants.Â Â Â